Composição química e digestibilidade do farelo de nabo forrageiro para tilápia do Nilo - Santos, Vivian Gomes dos [UNESP] (2010)
This study was conduced at the FMVZ – Unesp - Botucatu, to determine the Chemical composition and apparent digestibility coefficient (ADC) of dry matter (DM), crude protein (CP), raw energy (RE), amino acids (AA) and phosphorus availability. The fish were fed with a purified feed (base diet) and a 60% base diet plus 40% of fodder radish meal feed. Radish meal presented 91.28% DM, 42,07% CP, 4256 kcal/kg RE, 3.47% Ether extract, 7.37% crude fiber, 1.25% calcium and 1.0% phosphorus. The ADC values were DM: 55.92%, CP: 82.10%, RE: 75.26% and phosphorus: 85.23%. The ADC value for AA was 81.12% for glycine and 95.11% for glutamic acid. The results presented a potential utility for radish meal as an alternative protein source in Nile tilapia feeds.